Sistem Bagi Hasil dalam Perspektif Hukum Islam Antara Pemilik Kapal Nelayan dan Anak Buah Kapal di Desa Paloh Paciran Lamongan - R. Zainul Mushthofa; Siti Aminah (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2021)
The Muslim fishing community in Paloh Village, Paciran District, Lamongan Regency chooses and makes the sea a halal livelihood besides trading, because they liveon the coast of the Java sea. Almost all the men in the village work as crew members of fishing boats. For those who have capital, all the facilities and infrastructure at sea have been fulfilled, but for those who do not have capital, they are only members of a fishing boat. For those who do not have capital and want to become the leader of a fishing boat (Javanese: Jeragan), they seek capital not by borrowing money from banks or highrisk moneylenders, but looking for capital from rich people who want to build fishing boats for work. The principle of cooperation between fishing boat owners and skippers and their members already has arguments, which guide their lives as Muslims. The principle of cooperation that applies is whether it is completely in accordance with Islamic teachings or only partially or is it deviating, that is what the author needs to explore more deeply, so that the author intends to conduct this research.